Dysregulation of the haem-haemopexin axis is associated with severe malaria in a case–control study of Ugandan children. (December 2015) - Elphinstone, Robyn; Riley, Frank; Lin, Tian; Higgins, Sarah; Dhabangi, Aggrey; Musoke, Charles; Cserti-Gazdewich, Christine; Regan, Raymond; Warren, H.; Kain, Kevin
Abstract Background Malaria is associated with haemolysis and the release of plasma haem. Plasma haem can cause endothelial injury and organ dysfunction, and is normally scavenged by haemopexin to limit toxicity. It was hypothesized that dysregulation of the haem-haemopexin pathway contributes to severe and fatal malaria infections. Methods Plasma levels of haemin (oxidized haem), haemopexin, haptoglobin, and haemoglobin were quantified in a case–control study of Ugandan children withPlasmodium falciparum malaria. Levels at presentation were compared in children with uncomplicated malaria (UM; n = 29), severe malarial anaemia (SMA; n = 27) or cerebral malaria (CM; n = 31), and evaluated for utility in predicting fatal (n = 19) vs non-fatal (n = 39) outcomes in severe disease. A causal role for haemopexin was assessed in a pre-clinical model of experimental cerebral malaria (ECM), following disruption of mouse haemopexin gene (hpx) . Analysis was done using Kruskall Wallis tests, Mann–Whitney tests, log-rank tests for survival, and repeated measures ANOVA. Results In Ugandan children presenting withP. falciparum malaria, haemin levels were higher and haemopexin levels were lower in SMA and CM compared to children with UM (haemin, p < 0.01; haemopexin, p < 0.0001). Among all cases of severe malaria, elevated levels of haemin and cell-free haemoglobin at presentation were associated with subsequent mortality (p < 0.05). Compared to ECM-resistant BALB/c mice, susceptible C57BL/6 mice had lower circulating levels of haemopexin (p < 0.01), and targeted deletion of the haemopexin gene, hpx, resulted in increased mortality compared to their wild type littermates (p < 0.05). Conclusions These data indicate that plasma levels of haemin and haemopexin measured at presentation correlate with malaria severity and levels of haemin and cell-free haemoglobin predict outcome in paediatric severe malaria. Mechanistic studies in the ECM model support a causal role for the haem-haemopexin axis in ECM pathobiology.